RANCANG BANGUNG SISTEM MONITORING KUALITAS UDARA BERBASIS WEB MEMANFAATKAN MQ-135 DAN ARDUINO - Saputra, Aan; Diana (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2022)
Good air quality is needed by all living things. Air pollution can be bad for health. The absence of information and knowledge about air quality causes us to often ignore this problem. An application that can provide information in the form of good and bad thresholds of air quality can be used as a reference for preventing the adverse effects of air quality. This research has developed using the MQ-135 and Arduino. In principle, this tools works with the input from the MQ-135 air sensor then the results of this sensor will be sent to the Arduino microcontroller to be obtained according to the program created to then be displayed on a web page via a network connection conneted via the ESP8622 nodeMCU module so that the displayed results can be seen to the user. Application testing was carried out 4 time to measure the amount of CO2 level in the air based on the distance between the tool and the pollutant source dan wind direction. Test results and real time measurement of air pollutant levels can be displayed on the web so that it can be accessed by user. Based on the test results, it was found that the highest CO2 levels occurred when the pollutant source was 1 meter away from the pollutance source and the wind direction from the pollutant source to the tool. This shows thad the monitoring tool is working properly.